Optimalisasi Strategi Kinerja UMKM Pasca Pandemi dengan Pemanfaatan Media Informasi Pencatatan Keuangan - Muhammad Fitrah Mahaini; M Rizky Faadihilah; Altia Paradila Sapari (Universitas Kristen Maranatha, 2022)
This study aims to determine strategies for increasing the profitability of MSMEs through the use of financial recording information media. This study uses a qualitative method, namely a case study of one of the MSMEs engaged in the food sector in Palembang City with a sample of Ojisan Korean Street Food SMEs. The implementation is divided into several stages, namely the activity planning stage in the form of observations and interviews, training, stress testing analysis to determine the strategy for the business, and finally, evaluating the design's success. The owner of MSME Ojisan Korean Street Food said that the use of Excel as a financial recording medium for his business had a positive impact. Apart from more regular administration and finances, the resulting financial data can also provide forecasts and directions for determining the right strategy for the business. That way, the targeted profit will be easier to achieve. Keywords: SMEs, Microsoft Excel, Stress Testing, and Financial Recording